2020
DOI: 10.1101/2020.12.03.410175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure of the mature Rous sarcoma virus lattice reveals a role for IP6 in the formation of the capsid hexamer

Abstract: Inositol hexakisphosphate (IP6) is an assembly cofactor for HIV-1. We report here that IP6 is also used for assembly of Rous sarcoma virus (RSV), a retrovirus from a different genus. IP6 was ∼100-fold more potent at promoting RSV mature CA assembly than observed for HIV-1 and removal of IP6 in vivo reduced infectivity by 100-fold. By cryo-electron tomography and subtomogram averaging, mature virus-like particles (VLPs) showed an IP6-like density in the CA hexamer, coordinated by rings of six lysines and six ar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…Beyond HIV-1, IP6 has also been implicated as an assembly cofactor in other retroviruses, such as Rous sarcoma virus and equine infectious anemia virus. 71,72 It would be interesting to investigate the utility of IP6 and its derivatives for the efficient production of broad VLPs that have been repurposed for biomedical technologies, including vaccine development and biologics delivery. 73−76 Our results will hopefully stimulate future experimental studies as well as the use and development of even more sophisticated CG models.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Beyond HIV-1, IP6 has also been implicated as an assembly cofactor in other retroviruses, such as Rous sarcoma virus and equine infectious anemia virus. 71,72 It would be interesting to investigate the utility of IP6 and its derivatives for the efficient production of broad VLPs that have been repurposed for biomedical technologies, including vaccine development and biologics delivery. 73−76 Our results will hopefully stimulate future experimental studies as well as the use and development of even more sophisticated CG models.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Given the relationship between pentamers and lattice curvature, we speculated that pentamers could be enriched by forcing CA to form a high-curvature lattice similar to that permitted by pentamers at the ends of authentic capsid cores (3)(4)(5). Indeed, we and others have shown that CA from other retroviruses can be induced to assemble into highly-curved icosahedral particles enriched in pentamers under specific buffer and assembly conditions (36)(37)(38). For HIV-1, however, this is possible only with the introduction of mutations (39,40).…”
Section: Hiv-1 Ca Lattice Formation Via Protein Templating On Lipid V...mentioning
confidence: 99%
“…Additionally, since the crosscorrelation cleaning approach was not applicable when using Relion, we attempted to increase the homogeneity of the subvolumes used for refinement by a more stringent exclusion of subvolumes that deviate from ideal lattice geometry. In order to retain only subvolumes containing the structurally most similar local CA hexamers we employed a cleaning strategy based on local geometry, similar to what has been previously used for mature HIV-1 and RSV CA assemblies (Mattei et al, 2016; Obr et al, 2021) (see also Figure S4 and Materials & Methods for more details).…”
Section: Resultsmentioning
confidence: 99%
“…For this, we used an approach as employed in previous papers studying structures of retroviral Gag assemblies. This approach is based on tomogram reconstruction with 3D CTF correction using novaCTF and the AV3-derived subtomogram averaging/alignment pipeline (Dick et al, 2020; Förster et al, 2005; Obr et al, 2021; Turoňová et al, 2020, 2017).…”
Section: Introductionmentioning
confidence: 99%